2012
DOI: 10.1007/s11481-011-9339-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Decreases the Enzymatic Activity of Insulin Degrading Enzyme in APP/PS1 Mice

Abstract: Nitric oxide has been implicated in the regulation of enzyme activity, particularly the activity of metalloproteinases. Since the inducible form of the nitric oxide synthase (NOS2), is upregulated in Alzheimer's disease, we investigated the activity of two amyloid β degrading enzymes, IDE and neprilysin. In vitro we demonstrated that the activity of IDE was inhibited by *NO donor Sin-1, whereas activity of neprilysin remained unaffected. In vivo the activity of insulin-degrading enzyme was lowered in APP/PS1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…NOS2 also favors Aβ elimination by regulating MMP-9/TIMP-1 expression, which is a key enzyme that degrades amyloid (Ridnour et al, 2012). In addition, it has been shown that chronic NO formation may alter insulin-degrading enzyme activity (Kummer et al, 2012). NO synthesis during AD development could also contribute to NFT formation.…”
Section: Molecular Mediators Of Inflammation In Admentioning
confidence: 99%
“…NOS2 also favors Aβ elimination by regulating MMP-9/TIMP-1 expression, which is a key enzyme that degrades amyloid (Ridnour et al, 2012). In addition, it has been shown that chronic NO formation may alter insulin-degrading enzyme activity (Kummer et al, 2012). NO synthesis during AD development could also contribute to NFT formation.…”
Section: Molecular Mediators Of Inflammation In Admentioning
confidence: 99%
“…This data suggests that gal3 is a critical alarmin that amplifies the Aβ-induced proinflammatory response. Since inefficient clearance of Aβ may play a determinant role in AD pathogenesis [76], we analyzed the effect of gal3 in two major mechanisms associated to Aβ clearance: fAβ phagocytosis and IDE-1 levels, a key metalloprotease involved in Aβ degradation by microglia [25,28,39]. Gal3 was able to reduce Aβ phagocytosis, and gal3 deficiency increased IDE-1 levels, suggesting a detrimental role of gal3 in Aβ clearance.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that sustained proinflammatory molecules such as cytokines, chemokines, nitrogen reactive species (NRS) or reactive oxygen species (ROS) can create a neurotoxic environment driving the progression of AD [1,27,55,63]. Moreover, there is strong evidence supporting the role of inflammatory molecules, such as iNOS, in the initiation of plaque formation due to post-translational modifications of Αβ leading to a faster aggregation [38,39]. Indeed, counteracting the aggregation process has been proposed as a therapeutic strategy to alleviate the progression of the pathology [67].Conclusive evidence supporting a direct role of microglia in human neurodegeneration was revealed with the recent advent of massive genome analysis.…”
mentioning
confidence: 99%
“…In AD, activated glial are found clustered around amyloid plaques, and elevated levels of cytokines and other inflammatory mediators found in patients with AD have been proposed to contribute to ongoing pathology, neural dysfunction, and synaptic loss (Mrak and Griffin, 2005;Agostinho et al, 2010;Heneka et al, 2010). More recently, neuroinflammation has also been recognized as a potential part of normal aging (Lucin and Wyss-Coray, 2009;Jurgens and Johnson, 2010). Much research has therefore been aimed at understanding whether inflammatory processes are a causative or contributing factor to pathophysiology and memory loss in AD and cognitive decline that can occur in normal aging.…”
mentioning
confidence: 99%
“…Examining one of these mediators, nitric oxide, in an AD model, Kummer et al (2012) report primary in vitro and in vivo data demonstrating that nitric oxide synthesizing enzyme activity negatively regulates amyloid beta degrading enzymes. Montgomery and Bowers (2011) expound the current understanding of TNF alpha function within the CNS under normal physiologic conditions and how it changes with neurodegenerative disorders, particularly multiple sclerosis, AD and Parkinson's disease.…”
mentioning
confidence: 99%